Measurement and Mismeasurement of Social Development in Infants Later Diagnosed with Autism Spectrum Disorder - Klin, Ami; Jones, Warren (International Journal of Statistics in Medical Research, 2015)
Autism spectrum disorder (autism) is a common and heterogeneous neurodevelopmental disorder of genetic origins defined by challenges in social communication and clusters of restrictive and repetitive behaviors. An emerging hypothesis of autism pathogenesis describes symptoms as the results from deviations from normative developmental processes. In this account, symptoms represent the outcome of variable instantiation of genetic liabilities – in terms of dosage and timing – leading to disruptions in the developmental trajectories of foundational social adaptive skills. Given the fast pace of change in behavior and brain development in the first two years of life, we pose that the currently prevalent cross-sectional experimental designs are ill-suited to capture changes from normative benchmarks that might be small at any data point but which inexorably and cumulatively increase divergences in developmental trajectories that ultimately culminate in the unmistakable cluster of atypical behaviors we now call autism. We argue that only densely-sampled longitudinal experimental designs can capture the underlying dynamic processes moving the individual child’s development towards or away from normative benchmarks. We illustrate this phenomenon via a detailed example in which a cross-sectional comparison between a clinical and a control cohort failed to find differences, which could only be detected by ascertaining that the developmental trajectory of one cohort was moving upwards while the other was moving downwards, with the developmental lines intersecting at the cross-sectional data point. We conclude by magnifying Karmiloff-Smith’s assertion, oft-quoted but seldom followed, that “development itself is the key to understanding developmental disorders” [1].